Mayo and NINDS scales for assessment of tendon reflexes: between observer agreement and implications for communication. Issue 2 (1st February 1998) - Manschot, S; van Passel, L; Buskens, E; Algra, A; van Gijn, J
Abstract : The purpose of this study was to assess the between observer reliability of two standard notation scales for grading tendon reflexes, The Mayo Clinic scale and the NINDS scale. In a university department of neurology two or three physicians judged the biceps, triceps, knee, and ankle tendon reflexes in two groups of 50 patients using either scale. The interobserver agreement was assessed by means of κ statistics. The agreement among doctors was never better than "fair" for both scales (highest κ value 0.35). A verbal description rather than a codified scale may improve communication among doctors.